1978
DOI: 10.1111/j.1600-051x.1978.tb02280.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the in vivo and in vitro antibacterial properties of povidone iodine and chlorhexidine gluconate mouthrinses

Abstract: Clinical and laboratory studies were carried out to compare the antibacterial properties of two antiseptic mouthwashes, namely 1% povidone iodine and 0.2% chlorhexidine gluconate. In a group of 10 subjects after a single rinse with povidone iodine, an immediate mean fall in total salivary aerobes and anaerobes occurred, followed by a return to normal levels by 1-hour postrinsing. With chlorhexidine gluconate a similar but greater reduction in salivary bacterial counts was observed, which was still present up t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0
4

Year Published

1982
1982
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(48 citation statements)
references
References 17 publications
2
42
0
4
Order By: Relevance
“…The authors conclude that this antiseptic is very effective in reducing oral cavity bacterial counts up to 1 hour from the start of operation, which makes it suitable for shorter procedures (oral surgery in local anaesthesia). These results are supported by several smaller studies 1,7,21,23,36 . The authors also noticed that its favourable organo-leptic qualities are important when the oral cavity is preoperatively washed in awake patient.…”
Section: Discussionsupporting
confidence: 89%
“…The authors conclude that this antiseptic is very effective in reducing oral cavity bacterial counts up to 1 hour from the start of operation, which makes it suitable for shorter procedures (oral surgery in local anaesthesia). These results are supported by several smaller studies 1,7,21,23,36 . The authors also noticed that its favourable organo-leptic qualities are important when the oral cavity is preoperatively washed in awake patient.…”
Section: Discussionsupporting
confidence: 89%
“…6 Previous studies have showed that povidone iodine, as a mouthwash exerts only an immediate antibacterial effect and unlike chlorhexidine, is not retained at antibacterial levels within the oral cavity after expectoration. 13 In the present study, CTx4 treatment rinse mouthwash, which contains sodium fluoride as active ingredient and xylitol, sodium hypochlorite and sodium benzoate as inactive ingredients, is used. 0.2% sodium hypochlorite oral rinse is bactericidal to all bacteria on contact.…”
Section: -10mentioning
confidence: 99%
“…Since the introduction of chlorhexidine in the plaque control in the early 70s, several alternative plaque inhibitors with clear-eut effect as compared with placebo have been tested (5)(6)(7)(8). However, when compared with chlorhexidine none has shown equal or better activity without also giving unacceptable side effects (9)(10)(11)(12). Also chlorhexidine has some unpleasant side effects restricting its general use (13)(14)(15).…”
mentioning
confidence: 99%